General characteristics of departmental lawmaking activity of the Ministry of Internal Affairs of Ukraine - V. V. Korniienko (Law and Safety)
Problematic aspects of modern understanding of the category of “law formation” as a source for further scientific interpretation of the concepts of “lawmaking”, “departmental lawmaking” and “departmental regulations”, as well as a better understanding of the essence of lawmaking of the Ministry of Internal Affairs were studied. The aim of the research was to determine the basic requirements that must meet both departmental lawmaking of the Ministry of Internal Affairs of Ukraine and its end result such as departmental regulations, based on the fundamental aggregate conclusions of modern legal science in the study of “law formation”, “lawmaking”, “departmental lawmaking” and “departmental regulations”.